Survivalism, collectivism and proud heritage: A study of informal arts and crafts entrepreneurship in rural Zimbabwe - Sibusiswe P. Bango; Esinath Ndiweni; Laura Galloway; Helen Verhoeven (South African Journal of Business Management, 2018)
Background: Entrepreneurship has most often been studied in the context of developed economies and results extrapolated to apply universally. This tells us little about entrepreneurship in other contexts, including in developing economy situations. In the developing world, entrepreneurship has been explored as a means of reducing poverty, but there has been little inspection of it from other perspectives. Aim: This article explores the motives and experiences of arts and crafts traders in rural Zimbabwe and provides information about the purposes of the business for financial and social life from the perspectives of our research participants. Method: The study used a qualitative methodology, conducting interviews with 12 rural arts and crafts traders. Results: The research identifies drivers, experiences and outcomes of entrepreneurship that are explained by the unique structural and sociocultural context, and the value ascribed to business refers both to financial income and the dissemination of culture and heritage. Evidence of specific sub-Saharan modes of conducting business, reflecting the collectivity, reciprocity and strong ethnic identity characteristics of sub-Saharan African societies also emerges. Conclusion: The article illustrates that western models of business and entrepreneurship may be limited in terms of informing us about the experiences in other contexts. We argue that research on entrepreneurship, and any policy on it in sub-Saharan Africa, takes cognisance of the non-western context and the potential for unique contextual business orientation and outcomes.
Keywords: 650